2021
DOI: 10.18176/jiaci.0701
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Clinical Characteristics of Hereditary Angioedema Patients Who Experienced Attacks During COVID-19

Abstract: Supplementary material TABLE 1. Clinical, laboratory and psychiatric characteristics of HAE patients with C1INH deficiency or FXII mutation Patients HAE type Age/Sex long-term prophylactic care Annual attack (n) Comorbidities COVID-19 symptoms HAE attack localization Pulmonary involvement COVID-19 treatment D-dimer µgr/ml (0-440) CRP mg/dl(0-5) Lymphocyte 10 3 /µl (0.6-3.4) Fear during COVID-19 Fear, now CAS Psychiatric Impaired function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To date, there are minimal data available to answer these questions and address these concerns. Initial data from Brazil, France and Turkey showed no significant increase in HAE‐1/2 activity during or after COVID‐19, although some patients who were only using on‐demand therapy did report increased HAE activity 380–383 . A manuscript, in press, using the database of the HAE‐A demonstrated no evidence that HAE patients were at greater risk for infection or for serious infection, nor adverse effects to the vaccine.…”
Section: Patient Support Home Therapy and Self‐administration And Oth...mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are minimal data available to answer these questions and address these concerns. Initial data from Brazil, France and Turkey showed no significant increase in HAE‐1/2 activity during or after COVID‐19, although some patients who were only using on‐demand therapy did report increased HAE activity 380–383 . A manuscript, in press, using the database of the HAE‐A demonstrated no evidence that HAE patients were at greater risk for infection or for serious infection, nor adverse effects to the vaccine.…”
Section: Patient Support Home Therapy and Self‐administration And Oth...mentioning
confidence: 99%
“…[380][381][382][383] A manuscript, in press, using the database of the HAE-A demonstrated no evidence that HAE patients were at greater risk for infection or for serious infection, nor adverse effects to the vaccine. In a recent survey from the Netherlands, following 111 COVID-19 vaccine doses administered, 11 attacks were reported, six arose more than 48 h after vaccination.…”
mentioning
confidence: 99%
“…Initial data from Brazil, France, and Turkey showed no significant increase in HAE-1/2 activity during or after COVID-19, although some patients who were only using on-demand therapy did report increased HAE activity. 380 , 381 , 382 , 383 A manuscript, in press, using the database of the HAE-A demonstrated no evidence that HAE patients were at greater risk for infection or for serious infection, nor adverse effects to the vaccine. In a recent survey from the Netherlands, following 111 COVID-19 vaccine doses administered, 11 attacks were reported, 6 arose more than 48 h after vaccination.…”
Section: Patient Support Home Therapy and Self-administration And Oth...mentioning
confidence: 98%
“…However, studies support the possibility that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection may act as an attack trigger in patients with HAE, although attack severity was not affected 21,22 . Studies found that restriction measures during the pandemic were associated with an increased number of anxiety‐related HAE attacks, 23 and patients with HAE experienced increased fear and emotional distress during the pandemic 24 . There are conflicting data, however, as another study found there to be no significant difference in patients' Angioedema Quality of Life Questionnaire (AE‐QoL) scores or the frequency of HAE attacks in those with SARS‐CoV‐2 infection 25 …”
Section: Introductionmentioning
confidence: 99%
“…21,22 Studies found that restriction measures during the pandemic were associated with an increased number of anxiety-related HAE attacks, 23 and patients with HAE experienced increased fear and emotional distress during the pandemic. 24 There are conflicting data, however, as another study found there to be no significant difference in patients' Angioedema Quality of Life Questionnaire (AE-QoL) scores or the frequency of HAE attacks in those with SARS-CoV-2 infection. 25 In addition to potential effects on attack frequency and mental health, many challenges arose concerning communication between patients and physicians due to reduced face-to-face visits and additional measures to reduce virus transmission.…”
mentioning
confidence: 99%